Corporate governance structure, legal environment, and valuation - Sajid Gul; Abdul Rashid; Faqir Muhammad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This study consists of two separate sections; both sections can be read individually but share a common theme in Corporate Governance (CG). In the first section, a unique approach is presented to test whether the manner through which corporate governance structure influence stock market liquidity depends on countries' legal systems, using data from 10 emerging countries. Additionally, this study also examine whether legal institutions (i.e., judicial efficiency and political stability) enhances the level of investors participation and hence stock market liquidity. The second section seeks to explore the value relevance of firm level CG practices and legal origin. We employ governance rating consists of three categories. CG data and financial data covers the period 2003-2014. The final sample comprises of 644 firms from 10 countries. Ordinary Least Squares and System Generalized Method of Movement are employed to carry out the empirical analysis. The findings from the first section favor the hypothesis that firm-level governance structure and country's legal origin complements each other. We find evidence that as compared to common law countries, costs of liquidity are larger for companies in countries with civil law origin. This result implies that countries with common law origin have lower illiquidity, implying higher stock market liquidity. Nevertheless, the findings also indicate that although higher firm-level governance structure enhances liquidity of the stock market, this result for countries with civil law origin is weaker. Yet, the findings reveal that stock market liquidity is much higher in countries with higher political stability and judicial efficiency. The results from second section reveal that CG plays a positive and significant role in market valuation. Furthermore, the analysis indicates that CG is more important in enhancing firm value in countries with common origin as compared to the countries with civil origin. This study uses a broad CG measure to study its relation with stock market liquidity and market valuation, which has not been studied before, specifically in emerging markets. The findings of this study have important implications for managers, investors, and regulators, and may add significant contributions to the accounting and finance literature.
Keywords: 330; corporate governance; liquidity; firm value; judicial efficiency; political stability; CG score; volatility; stock market liquidity; emerging markets